ANALISIS STRATEGI KEWIRAUSAHAAN SOSIAL DALAMMEMBERDAYAAKAN MASYARAKAT - Intan Nurhusnaina; Rafita Sari; Siti Khopipah Harahap (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
The strategy in entrepreneurship aims to empower society. If an entrepreneur can carry out an entrepreneurial strategy seriously, there is a big possibility that success can be achieved and can bringabout change for himself. This research uses a literature study approach, by utilizing library sources toobtain research data. This research aims to increase understanding in creating social entrepreneurshipstrategies to empower the community. Entrepreneurial strategies that can be used to empower communitiescan start from economic empowerment, in order to provide individuals, groups or communities with access,knowledge, skills and resources they need to improve and manage their economic situation effectively.Community social empowerment , to emphasize that people have the capacity and potential to take controlof their own lives and play an active role in making decisions that will affect their lives. and communitycultural empowerment. This is an approach that seeks to strengthen, preserve and enhance the culturalheritage, traditions, language, arts and cultural values of a group or community. Apart from appropriatestrategies for empowering society, entrepreneurship principles are also needed..